Building Communities of Inquirers in Schools - Myriam Shechter (Networks: An Online Journal for Teacher Research, 1998)
Belonging to a community of inquirers makes you keenly aware of the benefits of such membership, as well as of the problems inherent to any larger group of people working together. Our own group of inquirers, DICEP (Developing Inquiring Communities in Education Project), associated with OISE/UT, includes university-based staff, teachers, and graduate students. We have created a large network of communication lines through which ideas, comments and suggestions flow freely between all participants: e-mail, meetings, interviews and, timepermitting, social get-togethers.